Length-weight relationship and condition factor of threadfin goby Sicyopterus longifilis de Beauford, 1912 (Teleostei: Sicydiinae) at Ummiding and Matama Rivers, West Sulawesi, Indonesia - TIKAWATI TIKAWATI; SHARIFUDDIN BIN ANDY OMAR; MUHAMMAD NUR (Society for Indonesian Biodiversity, 2024)
Abstract. Tikawati, Omar SBA, Nur M. 2024. Length-weight relationship and condition factor of threadfin goby Sicyopterus longifilis de Beauford, 1912 (Teleostei: Sicydiinae) at Ummiding and Matama Rivers, West Sulawesi, Indonesia. Biodiversitas 25: 2074-2085. Threadfin goby Sicyopterus longifilis (de Beaufort, 1912) is an amphidromous species known as 'penja' in the postlarval phase. Therefore, this research aimed to analyze the length-weight relationship and condition factors of goby fish in Ummiding and Matama Rivers, West Sulawesi. Fish sampling was conducted 12 times, twice monthly, during new and full lunar phases from July to December 2023. Each fish was measured for the total length, weighed, and dissected to determine the sex. The results showed that the length-weight relationship of goby fish in Ummiding River for male and female fishes were W = 0.000011L3.0250 and W= 0.000023L2.8422, respectively. In Matama River, the length-weight relationship for male and female fish was W = 0.000008 L3.1193 and W = 0.000005 L3.2228, with a combined sexes value of W = 0.000006 L3.1839. According to the statistical tests, the Ummiding River male fish had isometric growth due to a balanced length and body weight increase. In contrast, female fish had hypoallometric growth type (b<3), where the increase in length was faster than body weight. Male, female, and the combined sexes of the species in Matama River had hyperallometric growth type (b>3) since the increase in length was slower than body weight. The condition factor values exceeded 1.0, showing that Ummiding and Matama Rivers supported threadfin goby life. The acquired threadfin goby length-weight relationship and condition factors are now used as a guide for managing and conserving the species in this region.